2021
DOI: 10.1080/08927936.2021.1926708
|View full text |Cite
|
Sign up to set email alerts
|

From Pets to Pests: Testing the Scope of the “Pets as Ambassadors” Hypothesis

Abstract: Positive relationships with pets can sometimes foster more positive judgments of other animals. The present study sought to examine the scope of this "pets as ambassadors" effect in relation to four meaningful animal categories (companion, farmed, predator, and pest) derived from the Animal Images Database (Animal.ID). The Animal.ID contains ratings from 376 Portuguese individuals on pet attachment and several dimensions related to animal attributes and moral concern for 120 different animals, which offered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
4
7
0
Order By: Relevance
“…pet) ownership group when compared to both the limited experience and agricultural experience groups (with large and medium-large effects, respectively). These findings are consistent with previous studies concerning the effect caring for a pet has on empathic development towards animals (Paul 2000 ; Daly & Morton 2009 ; Auger & Amiot 2017 ; Martens et al 2019 ; Possidónio et al 2021 ; Vandersen & Hötzel 2021 ). Qualitative insights from the current study do suggest that first-hand pet ownership experiences may be an important factor explaining why this group possessed significantly higher empathy levels than the other two groups (see Table 3 ), providing support for the ‘Pets as Ambassadors’ hypothesis (Serpell & Paul 1994 ), but only if the pet owner is not also a farmer.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…pet) ownership group when compared to both the limited experience and agricultural experience groups (with large and medium-large effects, respectively). These findings are consistent with previous studies concerning the effect caring for a pet has on empathic development towards animals (Paul 2000 ; Daly & Morton 2009 ; Auger & Amiot 2017 ; Martens et al 2019 ; Possidónio et al 2021 ; Vandersen & Hötzel 2021 ). Qualitative insights from the current study do suggest that first-hand pet ownership experiences may be an important factor explaining why this group possessed significantly higher empathy levels than the other two groups (see Table 3 ), providing support for the ‘Pets as Ambassadors’ hypothesis (Serpell & Paul 1994 ), but only if the pet owner is not also a farmer.…”
Section: Discussionsupporting
confidence: 93%
“…However, Daly and Morton ( 2009 ) demonstrated that while pet ownership during childhood has a positive impact on AE, pet ownership during adulthood resulted in greater empathic gains, particularly for those who owned both cats and dogs. In adults, both pet contact and pet attachment have been associated with greater moral concern for a variety of animals, as well as decreased speciesism (Auger & Amiot 2017 ; Possidónio et al 2021 ). Pet ownership has also been associated with greater concern for pig welfare (particularly if the pet was viewed as “a child” or member of the family; Vandersen & Hötzel 2021 ), and a predictor of positive attitudes towards animals and greater concern for animal welfare (Martens et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, relationships between APQ, speciesism and likeability (Tisdell et al, 2005) ratings have yet to examined. The earlier study of positive evaluations (as measured by the animal images database) in relation to purpose of use did not extend beyond the 'acceptability to kill for human consumption' (and the moderating effect of pet ownership) assessed by Possidónio et al (2019Possidónio et al ( , 2021, and the categories related to purpose of use (Sevillano and Fiske, 2016;Leite et al, 2019).…”
mentioning
confidence: 92%
“…Speciesism has been compared to other forms of discrimination, such as racism and sexism, given that animals are treated differently based on simple biological differences between each other and humans (Lafollette and Shanks, 1996). Previous research has identified multiple factors which influence our attitudes to animal use, including the type of species and purpose of use (Bradley et al, 2020;Higgs et al, 2020), species likeability (perceptions of species' attractiveness, 'cuteness' and familiarity; Tisdell et al, 2005;Sevillano and Fiske, 2016;Possidónio et al, 2019Possidónio et al, , 2021, and participant characteristics such as gender (Caviola et al, 2019;Possidónio et al, 2019Possidónio et al, , 2021Bradley et al, 2020;Higgs et al, 2020) and age (Driscoll, 1992;Ormandy and Schuppli, 2014;Clemence and Leaman, 2016). Non-meat eaters attribute higher mental capacities to animals (Knight et al, 2009;Higgs et al, 2020), suggesting they show reduced tendency to dementalize certain species (Knight et al, 2004;Bilewicz et al, 2011;Morris et al, 2012;Hawkins and Williams, 2016;Higgs et al, 2020).…”
mentioning
confidence: 99%
“…This connection is possibly explained by the biophilia hypothesis, which asserts that the human dependence on nature “extends far beyond the simple issues of material and physical sustenance to encompass as well the human craving for aesthetic, intellectual, cognitive, and even spiritual meaning and satisfaction” ( Kellert, 1993 , p. 21), and therefore, the self-knowledge the environment provides, satisfies basic psychological needs ( Clayton, 2003 ). Identification with nature is also relevant to the pets as ambassadors hypothesis, initially proposed by Serpell and Paul (1994) , which states that owning pets during childhood may lead to positive attitudes toward animals in general, later in life, and to related behaviors, such as becoming members of animal welfare charities, and sometimes, by spill-over effects, even environmental and conservation organizations ( Serpell and Paul, 1994 ; Miura et al, 2002 ; Auger and Amiot, 2017 ; Possidónio et al, 2021 ). Concretely, our connection with nature is in part built on our interactions with animals and the natural world ( Clayton, 2003 ), and animals, in this view, can be considered as a bridge to the consideration and care of the natural world.…”
Section: Introductionmentioning
confidence: 99%